1991
DOI: 10.1182/blood.v77.8.1829.bloodjournal7781829
|View full text |Cite
|
Sign up to set email alerts
|

Autologous bone marrow transplantation in acute myelogenous leukemia: in vitro treatment with myeloid-specific monoclonal antibodies and drugs in combination

Abstract: We report the results of a preclinical study comparing four different purging protocols using a promyelocytic human cell line HL-60 and myeloid leukemic progenitor cells (colony-forming unit-leukemic [CFU- L]) from acute myelogenous leukemia (AML) patients assayed in semisolid culture. We studied the antileukemic effect of (1) Single-cycle complement-mediated lysis by two different monoclonal antibodies (MoAbs) (M195 [CD33] and F23 [CD13] 40 micrograms/mL), reactive with distinct antigens found on early myeloi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1993
1993
1994
1994

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…In control cultures an average of 27.7 rt 10% SD of CFU-GM in S phase within the stromal layer was observed at time of feeding (i.e., seven days after the last medium addition). This result is consistent with the data presented in our previous study [18]. The higher percentage of cycling progenitors compared with the previous study could be explained by the use of a different culture technique and by the lack of distinction among various myeloid colonies with regard to their size.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In control cultures an average of 27.7 rt 10% SD of CFU-GM in S phase within the stromal layer was observed at time of feeding (i.e., seven days after the last medium addition). This result is consistent with the data presented in our previous study [18]. The higher percentage of cycling progenitors compared with the previous study could be explained by the use of a different culture technique and by the lack of distinction among various myeloid colonies with regard to their size.…”
Section: Discussionsupporting
confidence: 93%
“…The cultures were established as previously described [18]. Briefly, red blood cell (RBC) depleted BM aspirates at concentrations of 3 x lo6 cells/ml were inoculated either in 25 cm2 tissue culture flasks (Falcon, Becton-Dickinson, Rutherford, NJ) or in gas-permeable plastic bags with a 300 ml capacity ("Lifecell" tissue culture [TC] bags; Fenwall Lab., Deerfield, IL).…”
Section: Culture Conditionsmentioning
confidence: 99%
“…Because M195 kills target cells with guinea pig and rabbit complement,' M195 has been used for ex vivo bone marrow purging of AML. 4 Although M195 is not intrinsically cytotoxic in vitro, an initial pilot trial of 10 patients with myeloid leukemias showed rapid and specific bone marrow targeting and efficient internalization of 1311-M195 into blast^.^ Using an optimal biologic dose of antibody for radioimmunotherapy from this original trial, a dose escalation trial of 13'I-M195 for relapsed or refractory myeloid leukemias was conducted and the results are described in this report. Safe, leukemic cytoreduction was seen with 13'I-M195.…”
Section: Murine and Humanized Constructs Of Monoclonal Antibody M I 9mentioning
confidence: 99%